Chinese Teaching in Chinese Department of Binus University - Khosasih, Andyni (Bina Nusantara University, 2011)
Binus University, established in 1974 and located in West Jakarta, is one of famous universities in Indonesia. This university has some literature departments including Chinese literature department which was started in 2002. At this moment, this department has 419 students and 28 lecturers who have different background. The difference of the students and lecturers’ point of view becomes one the backgrounds of this paper. The others are text books used, campus rules and alternative solution toward the problem faced. The method used in this research is direct observation. From the data taken and analyzed, it can be concluded: (1) Chinese department students, either Chinese descendant or not, has problems in learning Chinese, (2) The number of lecturers of Bachelor graduates is more than the master ones, (3) The Chinese language mastery of Chinese descendant students is better than non Chinese descendant ones, (4) The text books used are not all suitable for Chinese department student, and (5) The quality control system of Chinese teaching is good.